1983
DOI: 10.1111/j.1365-2052.1983.tb01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between rare breeds of sheep in the Netherlands as based on blood‐typing

Abstract: Genetic distances between seven Dutch rare breeds of sheep were established as based upon blood groups and biochemical polymorphisms. A rather close relationship was observed between three breeds of heath sheep (Drente, Veluwe and Kempen) and the Schoonebeker sheep. The Mergelland sheep was less related to this cluster. The largest distances were between Friesian sheep and Black Blaze sheep and all others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Manwell and Baker (1977) suggested that electrophoretic variants with low frequencies may represent, in many cases, relative recent mutations occurring after divergence of the breeds; this could be the case with the Balami breed. Akinyemi and Salako,(2012) also reported Tf P in Balami breed and the same was also reported for SardiandBeni Ashen sheep breeds in Morocco (Boujenane et al, 2008), and it is reported to be more widely distributed in European sheep breeds (Buis and Tucker, 1983;Zanotti et al, 1990).…”
Section: Transferrinmentioning
confidence: 56%
See 2 more Smart Citations
“…Manwell and Baker (1977) suggested that electrophoretic variants with low frequencies may represent, in many cases, relative recent mutations occurring after divergence of the breeds; this could be the case with the Balami breed. Akinyemi and Salako,(2012) also reported Tf P in Balami breed and the same was also reported for SardiandBeni Ashen sheep breeds in Morocco (Boujenane et al, 2008), and it is reported to be more widely distributed in European sheep breeds (Buis and Tucker, 1983;Zanotti et al, 1990).…”
Section: Transferrinmentioning
confidence: 56%
“…Similar results of predominance of Hb A had been reported for other sheep populations. Buis and Tucker (1983) found that in some Dutch breeds (Friesian, Schoonebeker, Drente and Kempen), Hb…”
Section: Haemoglobinmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies in sheep have already linked these markers to production traits and environmental adaptation (Vicovan and Rascu, 1989;Charon et al, 1996;Salakoet al, 2007). Information on blood proteins has also been extensively used for parentage control (Francois et al, 1992) and to study the genetic relationships among sheep breeds (Buis and Tucker, 1983;Ordas and San Primitivo, 1986;Mwacharoet al, 2002). However, the polymorphism of these important blood proteins had not being linked to survivability traits in the populations of sheep of Northern Nigeria (Balami, Uda and Yankasa sheep).…”
Section: Introductionmentioning
confidence: 99%